2016
DOI: 10.1093/hmg/ddw223
|View full text |Cite
|
Sign up to set email alerts
|

An intergenic risk locus containing an enhancer deletion in 2q35 modulates breast cancer risk by deregulating IGFBP5 expression

Abstract: Breast cancer is the most diagnosed malignancy and the second leading cause of cancer mortality in females. Previous association studies have identified variants on 2q35 associated with the risk of breast cancer. To identify functional susceptibility loci for breast cancer, we interrogated the 2q35 gene desert for chromatin architecture and functional variation correlated with gene expression. We report a novel intergenic breast cancer risk locus containing an enhancer copy number variation (enCNV; deletion) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 44 publications
0
37
1
Order By: Relevance
“…This is important as dysregulated IGFBP5 transcriptional control can act as a driver of cancer growth and metastasis, regulating cell proliferation, differentiation and metabolism using both IGF1R-dependent as well asindependent mechanisms of action (38,39). For example, copy number alterations encompassing an IGFBP5 enhancer on 2q35 modulate breast cancer risk (40). In melanoma, a recent preprint reported that inactivation of IGFBP5 distal enhancers down-regulates IGFBP5 expression and promotes melanomagenesis by inducing an IGF1R-AKT signalling-dependent increase in glycolysis and metabolic reprogramming (41).…”
Section: Discussionmentioning
confidence: 99%
“…This is important as dysregulated IGFBP5 transcriptional control can act as a driver of cancer growth and metastasis, regulating cell proliferation, differentiation and metabolism using both IGF1R-dependent as well asindependent mechanisms of action (38,39). For example, copy number alterations encompassing an IGFBP5 enhancer on 2q35 modulate breast cancer risk (40). In melanoma, a recent preprint reported that inactivation of IGFBP5 distal enhancers down-regulates IGFBP5 expression and promotes melanomagenesis by inducing an IGF1R-AKT signalling-dependent increase in glycolysis and metabolic reprogramming (41).…”
Section: Discussionmentioning
confidence: 99%
“…GWAS have identified 107 SNPs that are independently associated with breast cancer risk 232 . Association studies focused on ER-negative disease, or BRCA1 mutation carriers, who are more likely to develop ER-negative disease (70–80% of cases) 33 , have identified 11 of these SNPs 3,9,12,19,29,30 .…”
mentioning
confidence: 99%
“…One additional variant, rs11571833 at chromosome 13q13, was not genotyped and could not be imputed in all 3 studies; this variant had a minor allele frequency of 0.006 in the 1000 Genomes AFR population. These 74 risk variants include stronger markers than the index SNP found in GWAS as well as independent signals discovered through subsequent fine-mapping studies (Supplemental Table S1) (1, 3, 4, 8, 10, 11). …”
Section: Methodsmentioning
confidence: 99%